A prospective randomized study of use of drain versus no drain after burr-hole evacuation of chronic subdural hematoma - Velappan, Dhanapal Pattanam; Palaniappan, Ponnaiyan Natesan; Pandian, Anbarasi (International Surgery Journal, 2018)
Background: The incidence of chronic subdural hematoma is 1-2 per 100000 per year in the general population. Inserting subdural drain might reduce the recurrence rate but is not commonly practiced. There are few prospective studies to evaluate the effect of subdural drains. Methods: A prospective randomized study to investigate the effect of subdural drains in the on-recurrence rates and clinical outcome following burr-hole drainage of chronic subdural hematoma was undertaken. During the study period, 100 patients with CSDH were assessed for eligibility. Among 100 patients fulfilling the eligibility criteria, 52 were assigned to drain inserted into the subdural space following burr hole drainage and 48 were assigned subdural drain was not inserted following burr hole drainage. The primary end point was recurrence needing re-drainage and to prevent post-operative pneumocephalus up to a period of 6 months from surgery. Results: Recurrence occurred in 1 of 100 patients with a drain, and 9 of 100 patients in without drain group the medical and surgical complications were comparable between the two study groups. Conclusions: Use of a subdural drain after burr-hole evacuation of a chronic subdural hematoma reduces the recurrence rate and is not associated with increased complications.